FORMAÇÃO E VIDA: COMO ENFRENTAR O CANTO DAS SEREIAS? (Revista Apotheke, 2017)
The essay entitled “Formation and Life: how to face the siren’s song?” aims to reflect about modern’s formation process and its relation with the philosophical concepts approached by german philosopher Friedrich Nietzsche on the Untimely Meditation about the utilily and the inconvenients of History to life of 1874. The refered analysis present on his second untimely meditation, as well as the relation with the concept of transfiguration and the possibility of a education that turns to life’s horizon through an ethic and aesthetic perspective, taking into consideration an artistical thinking in detriment of a scientific formation.
Keywords: formation; life; art; ethic an asthetic; tranfiguration